ANALOGI SEBAGAI MEDIUM EFEKTIV UNTUK MENGENAL ALLAH: MENYELAMI KONSEP ANALOGI TIMBAL-BALIK - Den, Fidelis; Naibaho, Megawati (STIPAS St. Sirilus Ruteng, 2024)
God allows Himself to be known not only through speculative revelations but also through empirical facts in the universe. And man try to know God through the presence of the universe. The universe with all its contents in this context is understood not only as a representation of God, but He himself is within and at the same time transcends this universe. Belief in the universe as the imago dei is an argument that moves humans to find the divine vestigium in the world. God's initiative in letting Himself be known and man's efforts to know Him in creation are called a reciprocal analogy. Thus, analogy as an effective medium for knowing and talking about God refers to these basic assumptions. Because this research is in the category of descriptive qualitative research, data collection was carried out through the literature study method, by reading the latest books and journal articles. The data was then analyzed according to the main discussion in this article.